OPTIMALISASI SUMBER DAYA MANUSIA DAN SARANA PRASARANA UNTUK PENINGKATAN MUTU PELAYANAN KIA DI KABUPATEN POSO - Mariam Guru; Kodrat Pramudho; Resa Rerungan (Bajang Institute, 2025)
Maternal and child health (MCH) is a key indicator of public health development. Poso Regency continues to face challenges related to the limited and uneven distribution of health workers, as well as inadequate infrastructure for MCH services. This study aims to analyze the conditions of human resources (HR) and infrastructure, examine their relationship with service quality, and formulate optimization strategies for MCH services in Poso. This operational qualitative research involved 31 informants, including health office officials, primary health center heads, midwives, MCH program coordinators, cadres, and patients. Data were collected through in-depth interviews, focus group discussions (FGDs), and observations, and analyzed using Miles & Huberman’s interactive model. The findings revealed that shortages and unequal distribution of health workers, combined with limited infrastructure (such as the absence of ultrasound machines, incubators, and maternal-child ambulances), significantly reduced the quality of MCH services. The proposed optimization strategies include continuous training for health workers, redistribution of staff based on workload, provision of essential medical equipment, strengthening health cadres, and cross-sectoral coordination. This study highlights the importance of an integrated approach combining HR and infrastructure to enhance the quality of MCH services in Poso Regency.